The Functional outcome of arthroscopic anterior cruciate ligament reconstruction with hamstring graft - Khan, Muhammad Shahid; Azzam, Wael (Journal of Rawalpindi Medical College, 2023)
Introduction Incidence of anterior cruciate ligament (ACL) injuries is increasing owing to increased participation in sports. We are presenting our case series in which we have done ACL reconstruction (ACLR) with autologous hamstring graft. Basic idea for this project was to increase the awareness regarding timely management of ACL injury and good to excellent outcome of this minimal invasive technique. Materials and Methods In this retrospective study, we included 10 patients who underwent arthroscopic transportal single bundle ACLR using hamstring autograft, between January 2019 to December 2021 in Isra university hospital Hyderabad. Patients were followed routinely and outcome was recorded with the help of Lysholm knee scoring questionnaire at 6 months and 12 months post procedure. Results Mean age of the patients was 28.2 years (22 to 35 years) (Table-1). Average duration between injury to surgical intervention was 12.3 months (6 to 26 months). Final outcome was excellent in 3 patients (60%), good in 6 patients (30%) and fair in one patient (10%). Conclusion Injury to ACL is a critical event for any individual. Its timely management is important not only to return the patient back to pre-injury activity level but also to prevent delayed consequences of ACL tear. Our study and the literature review shows satisfactory results of arthroscopic ACLR. Finally, one should follow the basic principles of arthroscopic surgical technique of ACLR along with postoperative supervised physiotherapy rehabilitation protocol to get the desired results.